Pola Konsumsi Pasien Covid-19 yang Melakukan Isolasi Mandiri Selama PPKM Level 4 - Apris A. Adu; Daniela Boeky (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to determine the consumption patterns of COVID-19 patients during self-isolation at home during PPKM Level 4 in the city of Kupang. The research method is quantitative research with a cross-sectional study design. The results showed that the consumption pattern in terms of the type of food consumed was in the moderate category with a total of 46 respondents (57.5%); in terms of the amount of food in the excellent category with a total of 63 respondents (78.75%); and in terms of eating frequency, 72 respondents (90%). The amount of information about balanced nutritious foods makes isoman patients wiser in choosing and consuming foods to increase immunity and speed up the recovery process. In conclusion, getting food for COVID-19 patients during the PPKM level 4 in Kupang city, mainly obtained from family assistance, consumption patterns in categories, and the amount of food consumed, is good. Keywords: COVID-19, Independent Isolation, PPKM, Consumption Pattern